Perception Development of L2 English and L3 Polish Coda Obstruent by L1 German Adult Multilinguals - Romana Kopečková (Languages)
Research into L3 phonological acquisition has grown in the past decade, yet perceptual studies remain scarce. Existing studies report complex interactions between the phonetic categories of multilinguals’ L1, L2 and L3, depending on investigated feature and stage of L3 learning. This small-scale study, grounded in Complex Dynamic Systems Theory, examines the development of coda obstruent perception in seven beginner learners of Polish as an L3 (aged 21–39), with German as their L1 and English as their L2. Over ten months of instructed L3 learning, participants were tested four times using a timed forced-choice goodness task in both L2 and L3. Additionally, three participants provided monthly data between the second and fourth testing. Analyses across the sample revealed a competitive relationship between L2 and L3 perception, with L2 accuracy declining as L3 accuracy improved. Individual data, however, indicated more varied patterns: while one learner followed the overall trend, another exhibited decreasing accuracy in both their L2 and L3, and the third maintained accurate L2 perception alongside more accurate yet increasingly variable L3 perception. These findings highlight the value of analyzing both overall trends and individual data to better understand multilingual speech perception development, and suggest that, with growing L3 experience, the newly learnt L3 may influence L2 perception of a phonological process shared in the L1 and marked in the L2.